2017
DOI: 10.2196/humanfactors.7978
|View full text |Cite
|
Sign up to set email alerts
|

Workarounds Emerging From Electronic Health Record System Usage: Consequences for Patient Safety, Effectiveness of Care, and Efficiency of Care

Abstract: BackgroundHealth care providers resort to informal temporary practices known as workarounds for handling exceptions to normal workflow unintendedly imposed by electronic health record systems (EHRs). Although workarounds may seem favorable at first sight, they are generally suboptimal and may jeopardize patient safety, effectiveness of care, and efficiency of care.ObjectiveResearch into the scope and impact of EHR workarounds on patient care processes is scarce. This paper provides insight into the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 62 publications
2
129
0
1
Order By: Relevance
“…A lack of coherence between the wishes and expectations of healthcare providers, patients and technological capabilities could be the cause of this. Suggested is that, to avoid this, healthcare workers such as nurses, pharmacists and medical doctors should already be involved in the implementation phase of new IT‐based systems (Blijleven, Koelemeijer, Wetzels, & Jaspers, 2017; Koppel, Smith, Blythe, & Kothari, 2015; van der Veen, de Gier, van der Schaaf, Taxis, & van den Bemt, 2013). In our previous study in four hospitals in the Netherlands, we showed that workarounds are associated with medication administration errors (van der Veen, van den Bemt, Wouters, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of coherence between the wishes and expectations of healthcare providers, patients and technological capabilities could be the cause of this. Suggested is that, to avoid this, healthcare workers such as nurses, pharmacists and medical doctors should already be involved in the implementation phase of new IT‐based systems (Blijleven, Koelemeijer, Wetzels, & Jaspers, 2017; Koppel, Smith, Blythe, & Kothari, 2015; van der Veen, de Gier, van der Schaaf, Taxis, & van den Bemt, 2013). In our previous study in four hospitals in the Netherlands, we showed that workarounds are associated with medication administration errors (van der Veen, van den Bemt, Wouters, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…work-arounds (Blijleven, Koelemeijer, Wetzels, & Jaspers, 2017; Halbesleben, Wakefield, & Wakefield, 2008; Koppel, Wetterneck, Telles, & Karsh, 2008; Patterson, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that healthcare providers do not want EMR systems to disrupt their existing workflows and want them to integrate well into their work practices [15][16][17]. They want to easily navigate and find information in the EMRs [18][19][20] and need the EMR systems to support all of their formal [21,22] and informal documentation and communication tasks [23]. The shortcomings of previous EMR systems could be attributed to the task-focused mindset of early system implementers.…”
Section: Background-general Overview Of Emr Systems In Examination Roomsmentioning
confidence: 99%